Multifunctional Roles of MicroRNAs in Schistosomiasis - Zhong, Haoran; Jin, Yamei (Frontiers in Microbiology, 2022)
Schistosomiasis is a parasitic disease that is mainly induced by helminths of the genus Schistosoma. The dioecious schistosomes mate and lay eggs after undergoing a complex life cycle. Schistosome eggs are mostly responsible for the transmission of schistosomiasis and chronic fibrotic disease induced by egg antigens is the main cause of the high mortality rate. Currently, chemotherapy with praziquantel (PZQ) is the only effective treatment against schistosomiasis, although the potential of drug resistance remains a concern. Hence, there is an urgent demand for new and effective strategies to combat schistosomiasis, which is the second most prevalent parasitic disease after malaria. MicroRNAs (miRNAs) are small non-coding RNAs that play pivotal regulatory roles in many organisms, including the development and sexual maturation of schistosomes. Thus, miRNAs are potential targets for treatment of schistosomiasis. Moreover, miRNAs can serve as multifunctional “nano-tools” for cross-species delivery in order to regulate host-parasite interactions. In this review, the multifunctional roles of miRNAs in the growth and development of schistosomes are discussed. The various regulatory functions of host-derived and worm-derived miRNAs on the progression of schistosomiasis are also thoroughly addressed, especially the promotional and inhibitory effects on schistosome-induced liver fibrosis. Additionally, the potential of miRNAs as biomarkers for the diagnosis and treatment of schistosomiasis is considered.